Por que Laplanche? - Curi, Cristiane Abud; Haddad, Gisela; Majolo, Thiago; Zimmermann, Vera; Behr, Kenia M. Ballvé; Ceccarelli, Paulo Roberto (Percurso, 2016)
Realização: Cristiane Abud Curi, Gisela Haddad, Thiago Majolo e Vera Zimmermann